A decade of microbial community dynamics on sinking particles during high carbon export events in the eastern Fram Strait - Magda G. Cardozo-Mino; Ian Salter; Eva-Maria Nöthig; Katja Metfies; Simon Ramondenc; Claudia Wekerle; Thomas Krumpen; Antje Boetius; Christina Bienhold (Frontiers in Marine Science, 2023)
Marine sinking particles sequester atmospheric carbon dioxide to the deep ocean via the biological carbon pump. Understanding how environmental shifts drive changes in the microbial composition of particles, and how these affect the export of organic matter from the surface to the deep ocean, is critical, especially in the rapidly changing Arctic Ocean. Here, we applied next generation sequencing of the 18S and 16S rRNA genes to sediment trap samples from around 200 m water depth in the eastern Fram Strait, covering a time frame of more than one decade (2000-2012). The aim was to characterize their microbial composition during annual highest particulate organic carbon flux events. The bimodal annual spring and summer export fluxes were representative of the strong seasonality in the region. Furthermore, the study period was characterized by considerable interannual variation, marked especially by a warm water anomaly between 2005 and 2007. During this period changes in the hydrography and sea ice cover also led to measurable changes in the microbial composition of particles. The warm water period was marked by a decrease in diatoms affiliated with Chaetoceros , an increase of small phytoplankton and an increase in sequence abundance of the bacterial taxa Oceanospirillales , Alteromonadales and Rhodobacterales on the particles. The resulting changes in microbial composition and the associated microbial network structure suggest the emergence of a more developed retention system in the surface ocean. Our results provide the first long-term assessment of the microbial composition of sinking particles in the Arctic Ocean, and stress the importance of sea ice and hydrography for particle composition and subsequent flux of organic matter to deeper waters.